Medicinal cannabis: beyond the myth, just another (herbal) drug - Paulo Cáceres Guido (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2022)
This editorial briefly explores some of the distinctions between drugs and pharmaceuticals, alongside definitions regarding Cannabis sativa and its use in the context of a newly legal industry. Furthermore, medical cannabis is considered with regard to its toxicity, its social uses, its pharmacological activity, its legal paradoxes, and the scientific revolution sparked by the study of the endocannabinoid system, which has gained a great deal of relevance for modern physiology and pharmacology.